Twin grain boundary mediated ferromagnetic coupling in Co-doped ZnO: First-principles calculations. (January 2017) - Wu, Jingjing; Tang, Xin; Pu, Chunying; Long, Fei; Tang, Biyu
Abstract: First principle calculation, based on density functional theory, is applied to study the electronic and magnetic properties of Co-doped ZnO ∑7 (12 3 ̅ 0) twin grain boundary. Co atoms substituting Zn at the threefold-coordination sites have the lowest formation energy, compared with other sites. More importantly, the configuration can result in the stable formation of ferromagnetic state (FM). Meanwhile, the strong Co-Co interaction is found to be responsible for the ferromagnetic state. Due to the structural character of the twin grain boundary, periodical defects can be offered, which favors the macroscopic FM ordering. The result also gives us a new thinking to understand the origin of FM in transition metal doped ZnO. Highlights: The twin grain boundary can favor the formation of the Co-Co dimer in Co-doped ZnO. The dimer in FM state is 0.18 eV higher than that in AFM state. The twin grain boundary can mediate the FM coupling between the dimers. Due to the sructural character of the twin grain boundary, the macroscopic FM ordering is expected.